Promoting Social Creativity in Science Education With Digital Technology to Overcome Inequalities: A Scoping Review - Aguilar, David; Pifarre Turmo, Manoli (Frontiers in Psychology, 2019)
Enhancing creativity and developing technology skills in the classroom are the future of education and can turn out to be powerful tools to smooth out inequalities in class. This paper presents a systematic scoping review study of the literature focusing on cases of social creativity and digital technology embedded in science education. To this end, 23 empirical studies were selected from several databases—all in English and subjected to a blind peer-review process—to address the interconnectedness of key themes encapsulated in the following three research questions: (i) which digital technology roles support collaborative and creative processes in science education? (ii) which forms of technology and technological features support and organize the aforementioned creative processes? and (iii) what pedagogical principles guide the promotion of social creativity using technology in science education and involve all the students? Results show that technology can play different roles in promoting social creativity: (1) as a tutoring device that nurtures some key science creative processes; (2) as a tool that shapes students' creative thinking; and (3) as a medium that builds the supportive environment to perform collective creativity processes. In our project, these three roles were performed using a wide range of web 2.0 technologies (e.g., web-based environments, digital platforms, mobile technology) that both engaged all students in active and rich user experience for collective knowledge creation and equipped all learners with the necessary skills that would turn them into active, i.e., dynamic and resourceful, citizens in a swiftly changing world.